Pregnancy Metabolic Adaptation and Changes in Placental Metabolism in Preeclampsia - Li, Yaxi; Ma, Ling; He, Ruifen; Teng, Fei; Qin, Xue; Liang, Xiaolei; Wang, Jing (Geburtshilfe und Frauenheilkunde, 2024)
Pregnancy is a unique physiological state in which the maternal body undergoes a series of changes in the metabolism of glucose, lipids, amino acids, and other nutrients in order to adapt to the altered state of pregnancy and provide adequate nutrients for the fetus’ growth and development. The metabolism of various nutrients is regulated by one another in order to maintain homeostasis in the body. Failure to adapt to the altered physiological conditions of pregnancy can lead to a range of pregnancy issues, including fetal growth limitation and preeclampsia. A failure of metabolic adaptation during pregnancy is linked to the emergence of preeclampsia. The treatment of preeclampsia by focusing on metabolic changes may provide new therapeutic alternatives.
Keywords: pregnancy; metabolic adaptation; preeclampsia; placenta; glucose; lipids; amino acids